Respostas
respondido por:
1
Δ = b² - 4 x a x c
Δ = (-9)² - 4 x 1 x 20
Δ = 81 - 80
Δ = 1
x = (-b ± √Δ) / 2 x a
x' = (-(-9) + √1) / 2 x 1
x' = (9 + 1) / 2
x' = 10 / 2
x' = 5
x'' = (-(-9) - √1) / 2 x 1)
x'' = (9 - 1) / 2
x'' = 8 / 2
x'' = 4
S = {5; 4}
Δ = (-9)² - 4 x 1 x 20
Δ = 81 - 80
Δ = 1
x = (-b ± √Δ) / 2 x a
x' = (-(-9) + √1) / 2 x 1
x' = (9 + 1) / 2
x' = 10 / 2
x' = 5
x'' = (-(-9) - √1) / 2 x 1)
x'' = (9 - 1) / 2
x'' = 8 / 2
x'' = 4
S = {5; 4}
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás